An Effectiveness of Emotional and Social Intelligence Intervention (Stress Tolerance) - Laila Wati Madlan; Chua, Bee Seok; Murnizam Halik; Jasmine Adela Mutang; Muhammad Idris Bullare (2018)
This research to investigate whether emotional intelligence developmental training can lead to increase with the Module of Emotional and Social Intelligence (Stress Tolerance). A study with quasi-design was employed with self-report assessment conducted as baseline and posttest following 14 weeks training programmed. The Faculty of psychology and Education, University Malaysia Sabah students participated in the study, and 19 students were recruited to the experiment group and receive the intervention. Meanwhile, 21 students were recruited to the control group. Recruitment based on the lower score on emotional Quotient inventory (EQ-i). The result of this finding reported that Stress Tolerance subscale had increase in mean score after intervention. A conclusion, most of the emotional intelligence training had a positive effect on the students in intervention group. While, there is no different score between control group for pre and post intervention.